Global justice and international affairs - Brooks, Thom (Studies in moral philosophy (Leiden, Netherlands) ;, 2012)
Global justice and international affairs is perhaps the hottest topic in political philosophy today. This book brings together some of the most important essays in this area. Topics include sovereignty and self-determination, cosmopolitanism and nationalism, global poverty and international distributive justice, and war and terrorism.